Evaluation of Toluene Vapors on the Hearing System of a Production Company Employee: A carcinogenic agent - Nikpay, Ahmad; Moradi, Reza; Sheikhi, Salman; Mousavi Jarrahi, Seyedeh Zahra; Jaddi Madarsara, Tayyebeh; Saeidabadi, hamzeh (Asian Pacific Journal of Environment and Cancer, 2019)
Introduction: Hearing loss is one of the most common causes of disability of more than 1.33 billion people worldwide and, according to WHO research, failure to timely detect hearing loss has detrimental effects on the individual, the family and the world economy ($ 750 billion), Therefore, exposure to excessive noise and exposure to organic solvents can cause hearing loss in individuals. Methods: This descriptive-analytical study was performed on a manufacturing company with a statistical population of 17 people (8 employees of printing and electroplating unit with a mean age of 40±4.78 and 9 employees of Coldwell unit with a mean age of 4.33±41). Data were analyzed by SPSS software version 16 and paired T-test. Results: According to the pollutant results in the Coldwell unit, the noise level was exceeded, but the toluene levels were measured at the permissible level, which, according to the software output, showed a faster rate of hearing loss (Right ear sig = 0.007 and left ear sig = 0.002) and also, in the printing and plating unit, the sound level was above the permissible limit, but the toluene level was exceeded, which according to the software output of these units had a lower rate of hearing loss. Conclusion: The results of this study show that simultaneous exposure to noise and organic solvents such as toluene in the workplace accelerates the Occupational Hearing Loss Process, as well as employees who are not exposed to noise, are reasonably hearing impaired due to exposure to toluene. keywords: Noise, Audiometry, Occupational Hearing Loss, Measurement of Workplace Hazardous Factors, Organic Solvent Vapor, Toluene Vapor.